The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2000
DOI: 10.1007/s11934-000-0052-y
|View full text |Cite
|
Sign up to set email alerts
|

Microbiology of the Prostate

Abstract: Prostatitis is a common genitourinary disease in men. The National Institutes of Health has defined four types of prostatitis. The bacteriology of acute and chronic bacterial prostatitis is well understood. Causative organisms can be isolated by four-glass urine cultures. Chronic pelvic pain syndrome (CPPS; chronic abacterial prostatitis) is an enigma; whether there is a microbiologic cause for this condition is unknown. Researchers have postulated that CPPS may be an infectious disease of the prostate. This a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Mechanistic understandings of a number of diseases that are believed to have microbial axes have escaped conventional biological analyses [1]–[3]. The application of integrative systems biology approaches exploiting multiple data sources holds much promise in developing a fuller understanding of these diseases [4], [5].…”
Section: Introductionmentioning
confidence: 99%
“…Mechanistic understandings of a number of diseases that are believed to have microbial axes have escaped conventional biological analyses [1]–[3]. The application of integrative systems biology approaches exploiting multiple data sources holds much promise in developing a fuller understanding of these diseases [4], [5].…”
Section: Introductionmentioning
confidence: 99%
“…Approximately a quarter of the ejaculate is composed of secretions produced by the prostatic epithelium [ 31 ]. While previous studies suggested the existence of a prostate microbiota [ 32 , 33 ], only studies relying on NGS could reveal an unbiased composition of the bacterial taxa ( Table 1 ).…”
Section: Microbiota Of the Mgtmentioning
confidence: 98%
“…It was found that gram positive Staphylococci species involved in the pathogenesis of chronic pelvic pain syndrome[18]. They were identified in the focal colonies adherent to the prostatic duct walls[19]. Bergman demonstrated that gram positive Staphylococci species were found in significant numbers in 43% of patients with symptoms of prostatitis[20].…”
mentioning
confidence: 99%